L’art du théâtre de Howard Barker : la scène et la page en conflit - Vanasay Khamphommala (Sillages Critiques)
In his essays, Barker opposes the materiality of the theatre, that he despises, and the ideal of the art of theatre, to which he aspires. This distinction is best seen in his treatment of the dramatic text, both an object of fantasy in its written aspects, and an object of suspicion in its vocal dimension. This paper examines how Barker concentrates these tensions around the object the book, an omnipresent element of his imagination and plays, to the point of threatening the stage itself as a better, if paradoxical, dramatic space.